2003
DOI: 10.5694/j.1326-5377.2003.tb05655.x
|View full text |Cite
|
Sign up to set email alerts
|

3: Preventing complications of diabetes

Abstract: Diabetes complications are common and almost triple the annual cost of managing diabetes. Microvascular complications are the major risk in type 1 diabetes, while macrovascular complications are the major cause of morbidity and mortality in type 2 diabetes. Control of hyperglycaemia (target HbA1c level ≤ 7%) and hypertension (target blood pressure ≤ 130/80 mmHg) prevents microvascular complications in both types of diabetes; a multifactorial approach, comprising behaviour modification and pharmacological thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…The drop in blood pressure and the rise in HDL cholesterol level with SGLT2 inhibitor therapy could even make SGLT2 inhibitors more promising. This is because; in patients with type 2 diabetes the major cause of morbidity and mortality is attributed to cardiovascular diseases [4,37]. But SGLT2 inhibitors long term effects on cardiovascular outcomes is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drop in blood pressure and the rise in HDL cholesterol level with SGLT2 inhibitor therapy could even make SGLT2 inhibitors more promising. This is because; in patients with type 2 diabetes the major cause of morbidity and mortality is attributed to cardiovascular diseases [4,37]. But SGLT2 inhibitors long term effects on cardiovascular outcomes is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular complications like diabetic retinopathy, nephropathy, and neuropathy are major causes of new cases of blindness and renal insufficiency [3]. Moreover, in type 2 diabetes macrovascular complications, including coronary heart disease and stroke, are major causes of morbidity and mortality [4]. According to a prospective study, in patients with type 2 diabetes, a 1% increase in HbA1c was associated with 20% to 30% increase in mortality or cardiovascular events [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a major complication and the leading cause of premature death among patients with diabetes (Centers for Disease Control and Prevention, 1999). The primary risk factor for CVD among patients with type 1 diabetes is hyperglycemia, although other risk factors, such as hypertension and dyslipidemia, may occur secondary to uncontrolled hyperglycemia (Bate & Jerums, 2003). In contrast, the pathophysiology of cardiovascular complications of type 2 diabetes involves elements of hyperglycemia, dyslipidemia, hypertension, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, we have shown that Tst (in adrenal) and Trak2 (skeletal muscle) transcript levels correlate with traits associated with fat metabolism and colocalize with pQTLs for lipid level and body weight, while Hpx (adrenal) and Pex11b (fat) represent c3-eQTLs relating to blood sugar regulation and traits recognized as downstream consequences of abnormal blood sugar regulation (4, 10, 55, 64) (Supplementary Table S6). These c3-eQTLs are particularly striking given that they also occur in tissues that are physiologically relevant for the control of these traits, suggesting that they represent strong candidate genes underlying these phenotypes in the SHR.…”
Section: Discussionmentioning
confidence: 83%